Is There an Association Between the "Critical Shoulder Angle" and Clinical Outcome After Rotator Cuff Repair?. Issue 4 (18th April 2017) - Kirsch, Jacob M.; Nathani, Amit; Robbins, Christopher B.; Gagnier, Joel J.; Bedi, Asheesh; Miller, Bruce S.
Background: Variations in scapular morphology have been associated with the development of atraumatic rotator cuff tears (RCTs). The critical shoulder angle (CSA) accounts for both glenoid inclination and lateral extension of the acromion. The impact of the CSA on outcomes after rotator cuff repair (RCR) has not been investigated previously. Hypothesis: Our hypothesis was that individuals with smaller CSAs will have better patient-reported outcome scores over time compared with those with larger CSAs. Theoretically, a smaller CSA minimizes the biomechanical forces favoring superior translation of the humeral head, which may be advantageous after RCR. This is the first study to examine the relationship between the CSA and clinical outcomes after RCR. Study Design: Cohort study; Level of evidence, 2. Methods: Fifty-three patients (mean age, 61 years) with atraumatic full-thickness RCTs who underwent arthroscopic RCR were prospectively evaluated. Demographic data as well as the Western Ontario Rotator Cuff Index (WORC) score, American Shoulder and Elbow Surgeons (ASES) score, and a visual analog scale (VAS) for pain were prospectively collected at various time points up to 24 months postoperatively. Statistical analysis included longitudinal multilevel regression modeling to investigate the association between the CSA and the WORC, ASES, and VAS scores. Results: The overall clinical outcome, as measured by the WORC, ASES, and VAS, improved significantly ( P < .0001). Controlling for demographic and clinical characteristics, a multilevel regression analysis demonstrated that the CSA was not a significant independent predictor for change in WORC ( P = .581), ASES ( P = .458), or VAS ( P = .859) scores at 24 months after arthroscopic RCR. Interobserver and intraobserver reliability for CSA measurements resulted in interclass correlation coefficients of 0.986 and 0.982, respectively ( P < .001), indicating excellent agreement. Conclusion: The CSA did not appear to be a significant predictor of patient-reported outcomes after arthroscopic repair of atraumatic full-thickness RCTs.